Geographic and social movement of sex offender fugitives - Bierie, David M. (Crime & delinquency, 2016)
The Adam Walsh Child Protection and Safety Act (AWA) established the U.S. Marshals Service (USMS) as the nation’s lead agency in the pursuit of sex offenders who violate a sex offender registry and cross state, tribal, or national borders. This study examines the flight behavior of 195 AWA violators investigated by the USMS during 2011 and focuses on the strategic choices fugitives made including the distance offenders traveled, whether they lived alone or with others at capture, and whether they were arrested in a community they were familiar with (e.g., a city they had lived in before). A number of personal, criminal, geographic, and social indicators were taken from law enforcement and public records in an effort to model patterns across these three strategic choices. The data showed that 37% of AWA violators fled to a familiar area, 65% lived with friends or family at capture, and 50% traveled more than 370 miles (with 35% residing in an adjacent state to the last known address). Analyses also showed that these three outcomes varied as a function of offender demographics, geographic history, social networks, and criminal history. Implications for policy and research are discussed.